Efek Permainan Edukatif oleh Teman Sebaya Terhadap Pengetahuan Kesehatan Reproduksi, HIV-AIDS, dan NAPZA - Intan Farida Yasmin; Dicky Adi Putra; Lia Fristka; Jimmi Lihartanadi; Matt Biondi; Ayu Kartika Sari; Alain Laurent; Christiani Christiani (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: Here we intend to analyze the effects of educative games provided by peer groups as method to increase knowledge of reproductive health, HIV-AIDS, drugs abuse among high school students. Method: Twenty students (peer-counselor group) of junior high school in Keruak, East Lombok were educated using boardgames and series of flashcards containing information of reproductive health, HIV-AIDS, and drugs abuse before they educated other students (non-counselor group, n=119) using the same educative game. Pre and post scores analysis was conducted among both groups. Results: The post-game scores of both peer-counselor and non-counselor groups were increased significantly after playing boardgames and flashcards. The non-counselor group gained 1.9-fold, 2.6-fold, and 4.5-fold increase of post-game scores compared to pre-game scores (p < 0.01) in reproductive health, HIV-AIDS, and drug abuse topics respectively. After completing the educative games, the proportion of students who had high level of knowledge about reproductive health, HIV-AIDS, and drug abuse was increased significantly (0% to 26.9% p <0.01, 3.4% to 26.9% p <0.01, 18.5% to 61.3% p <0.01, respectively). Conclusion: Using educative games and peer-group approach as health promotion method were proven to increase knowledge in reproductive health, HIV-AIDS, and drug abuse among adolescent students. In the future, this method could be adapted nationally as part of educational health promotion program.